Methods for evaluating the effectiveness of logistics support for groups of heterogeneous forces (troops) - Avramenko , Oleksandr; Kotsyuruba , Volodymyr; Datsenko , Ivan (Social Development and Security, 2021)
The occupation of Crimea and the Russian Federation’s support for separatist movements in the Luhansk and Donetsk regions showed the fallacy of the until recently current assessments of the military-political situation that has developed around Ukraine, as well as internal and external threats to the national interests of the state. An analysis of the anti-terrorist operation in the Donetsk and Lugansk regions (Operation of the Joint Forces) shows that the system of logistics, technical, medical and other types of support needed to be quickly adapted to the real situation, forms and methods of using units (subdivisions) at different stages of its implementation. In the context of European integration and new tasks of the Armed Forces of Ukraine related to the participation of Ukraine in anti-terrorist operations, in peacekeeping activities under the auspices of NATO and the UN, there is a need to reform the troops (forces), types of logistics, technical and medical support in accordance with the requirements of NATO standards. This article has developed a methodology for assessing the effectiveness of logistical support for a grouping of heterogeneous forces (troops) of the Naval Forces in a special period. In the course of the research conducted by the authors, the basic provisions of the theory of complex technical systems, the theory of artificial intelligence, the taxonomic method, as well as general scientific methods of analysis and synthesis were used. The above methodology makes it possible to evaluate the effectiveness of the logistics support system for a grouping of heterogeneous forces (troops) of the Naval Forces in a special period, to determine measures aimed at improving logistics support. On the basis of this methodology, the authors will develop recommendations for improving the logistics support for the grouping of heterogeneous forces (troops) of the Naval Forces in the Azov operational zone in a special period.